Textural Differentiation of the Old Arable Horizons of Uneven-Aged Fallow Light-Gray Forest Soils - K.G. Giniyatullin; M.R. Khuzieva; R.V. Okunev; E.V. Smirnova (Учёные записки Казанского университета: Серия Естественные науки)
Differentiation of the old arable horizons of uneven-aged (70–75 and 2 years) fallow light-gray soils by the content of < 0.01 and < 0.001 mm fractions, as well as by the total content of some rock forming elements was studied. The results demonstrated that the textural differentiation cannot be revealed by the traditional methods for determining the content of granulometric fractions with the use of sodium pyrophosphate to disaggregate soil particles due to the masking effect of newly formed organic matter under the fallows. Application of the methods for determining the content of fine granulometric fractions, which are conditioned by organic matter removal with H2O2 treatment, makes it possible to trace the statistically significant increase in the content of fine fractions in the lower part of the old arable horizons at the expense of its reduction in the upper part. The textural differentiation of the old arable horizon by granulometric composition corresponds to the changes in its total elemental composition. Based on the obtained results, it was concluded that the process of suspended transfer of fine mineral particles (known as “agrolessivage” for arable soils) as arable soils are converted in fallows continues over a long period of time and leads to significant differentiation of the old-arable horizon, which deepens with the fallow age.